Penetapan Dispensasi Nikah Oleh Hakim (Studi Komparatif Hukum Islam Dan Hukum Positif) - Imam Syafi’i; Freede Intang Chaosa (Mabahits : Jurnal Hukum Keluarga Islam, 2021)
This research is to examine the dispensation of marriage which is a policy or legal aid provided by the Religious Courts to prospective brides and grooms, one or both of whom have not reached the age requirement in Law No. 1 of 1974. In the decision, a judge is guided by the Marriage Law, Islamic Law Compilation, Supreme Court Regulation No. 5 of 2019, also the Minister of Religion Regulation No. 11 of 2007 concerning Marriage Registration. The judge considers all aspects of life before giving a decision to grant or reject a dispensation case, including aspects of age maturity and self-maturity, health aspects, economic aspects, whether or not there is an element of compulsion to marry and other aspects that are considered important to be considered before getting married.